2015
DOI: 10.1371/journal.pone.0118174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paricalcitol vs Calcitriol on Hemoglobin Levels in Chronic Kidney Disease Patients: A Randomized Trial

Abstract: BackgroundRecent studies suggest that vitamin D deficiency represents an additional cofactor of renal anemia, with several mechanisms accounting for this relationship. In line with it, the administration of vitamin D or its analogues has been associated with an improvement of anemia. There are no data, however, about a direct effect of paricalcitol on hemoglobin (Hb) levels. Therefore, we conducted a study to determine whether paricalcitol, compared to calcitriol, improves anemia in patients with chronic kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Riccio et al [15] also demonstrated that paricalcitol exhibited beneficial effects on hemoglobin levels in patients with advanced-stage CKD, independently of other factors such as inflammation or PTH levels.…”
Section: Discussionmentioning
confidence: 96%
“…Riccio et al [15] also demonstrated that paricalcitol exhibited beneficial effects on hemoglobin levels in patients with advanced-stage CKD, independently of other factors such as inflammation or PTH levels.…”
Section: Discussionmentioning
confidence: 96%
“…Among those that have, the results have been mixed, likely due to the differences in dosage and form of vitamin D administered, and the population studied [26-28]. In studies of patients with CKD, vitamin D or its analogues have been shown to increase hemoglobin concentrations [27, 29-31]. Larger studies examining the effect of vitamin D administration on circulating hepcidin concentrations, and the subsequent impact on hemoglobin concentrations or anemia in both healthy and diseased populations at risk for anemia are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with several studies in chronic kidney disease, cardiovascular disease, and the general population, which have described a positive association between vitamin D status and hemoglobin and/or an inverse association between vitamin D status and anemia (913, 15, 39, 40). Data from clinical trials have been mixed (3942), but recent studies in CKD and critically ill adult patient populations found that treatment with vitamin D or its analogues resulted in significant increases in hemoglobin concentrations (24, 43). This association has not been previously studied in IBD animal models or clinical studies.…”
Section: Discussionmentioning
confidence: 99%